Formulation of quality fish feeds from indigenous raw materials and their effects on growth and maturity of Mystus gulio (Journal of the Bangladesh Agricultural University, 2010)
An experiment was conducted for 140 days in earthen ponds to evaluate the effect of three dietary protein levels on the growth and maturity of bagrid catfish Mystus gulio. Three different iso-caloric feeds containing 30%, 35% and 40% dietary protein levels were prepared from indigenous fish feed ingredients and were fed to Mystus gulio at the rate of 5% of total body weight of the fish. The overall growth of Mystus gulio fed with feeds of different levels of dietary protein was found to increase with the increase of dietary protein levels in the feed. The gonadosomatic index (GSI) values of both male and female were higher in Feed-C (40% protein) compared to the Feed-A (30%) and Feed-B (35%). There was significant differences (P